QUALITY OF CRUDE PROTEIN AND ORGANOLEPTIC PROPERTIES OF FRIED MILK MADE FROM GOAT MILK WITH PLAIN YOGURT AS A COAGULANT - Umbang Arif Rokhayati; Tri Ananda Erwin Nugroho (JIM - Journal International Multidisciplinary, 2025)
Fried milk is a traditional dairy product made from goat's milk. This research was conducted at the Animal Products Technology Laboratory, Department of Animal Science, Faculty of Agriculture, Universitas Negeri Gorontalo, from October to November 2025. The purpose of this study was to determine the effect of using papain as a coagulant on the crude protein and organoleptic properties of fried milk made from goat's milk. The research used a Completely Randomized Design (CRD) with 4 treatments and 3 replications. The treatments were as follows: P1: Papaya sap 0.05% + plain yogurt 1% of milk volume, P2: Papaya sap 0.05% + plain yogurt 1.5% of milk volume, P3: Papaya sap 0.5% + plain yogurt 2% of milk volume, P4: Papaya sap 0.5% + plain yogurt 2.5% of milk volume. The variables studied include crude protein content and organoleptic tests (color, taste, aroma, and texture). The research results show that the treatment significantly affects crude protein (P<0.05) and produces a slightly fine texture, color, taste, and aroma of fried milk that is preferred by the panelists. The best results for fried milk were obtained with treatment P3: 0.5% Papaya sap + 2% plain yogurt by milk volume, and P4: 0.5% Papaya sap + 2.5% plain yogurt by milk volume.